PERCEPTIONS OF SERVICE-ORIENTATION AND TRUST OF TAX OFFICERS BETWEEN MILLENIALS, X, AND BABY BOOMERS - Elisa Tjondro; Kezia Gabriel Santosa; Nathasa Prayitno (Universitas Mercu Buana, 2019)
The purpose of this study is to examine differences in perceptions of generations related to service-orientation and trust to tax officers. Changes traditional paradigm of the relationship between tax officers and taxpayers from “cops and robbers” to